Data Analysis and Processing for Law Students —Taking the General Course of Legal Data Analysis and Processing as an Example - Li, Weiwei; Chen, Qi (Journal of Educational Research and Policies, 2025)
With the rapid development of big data and artificial intelligence (AI) technology, how to improve the information literacy ability of liberal arts students is the current focus and difficulty in the cultivation of new liberal arts talents. In this paper, taking law students as an example, combined with the authors’ teaching and research practice, we take the simple and precise data analysis ability as the teaching goal, and construct a course content framework suitable for law students. The course mainly carries out some explorations and reflections on the teaching content, teaching methods, experimental cases, etc., aiming to provide reference for the cultivation of liberal arts talents in the new era.